Penguatan Human Security sebagai Strategi Pengelolaan Perbatasan Indonesia-Malaysia - Yohanes Sanak (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2012)
This paper discusses the importance of strengthening human security strategy at the border of Indonesia and Malaysia as a way to realize national interests. Using a case study design and qualitative approach, this paper attempt to explain the conditions of human security in border’s area. Some problems such as low level of people welfare indicates that individual security at the border is still unstbale. Underlying this argument, the government should implement the strategy of strengthening human security in border management. Through the strengthening of individual security, people’s natonalism will be strong to support the state. This strategy enough feasible to be implemented because Indonesia and Malaysia are neighboring and friendly countries, prominence of individual security issues, the cultural similarities and the failure of the implementation of the strategy of prioritizing state security.